2014
DOI: 10.7243/2053-5775-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Ion exchanges between glass-ionomer restorative material and primary teeth components-an in vivo study

Abstract: Objectives: To analyze the ion exchange between conventional glass-ionomer restorative material, (Fuji IX-GC Co., Japan) and tooth components in primary molars after long periods of function in vivo. Methods: Five deciduous mandibular molars were collected after normal exfoliation. An intact deciduous molar served as control, a second deciduous molar was restored occlusaly with Fuji IX in vitro, and 3 deciduous molars with occlusal restorations were collected after 18, 24, and 48 months in vivo. The molars wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
2
8
0
1
Order By: Relevance
“…The potential of remineralization of carious lesions in dentin in vitro by glass-ionomer cements (GIC) has been long established, and related to the release of fluoride ions from the restorative material. Diffusion of additional ions from GIC, like calcium, and phosphate has an additional effect on remineralized dentin in vivo in permanent teeth (26) . Those results are in agreement with others studies (27,28) , which showed significant remineralization effect of Nano glass ionomer on dentin.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of remineralization of carious lesions in dentin in vitro by glass-ionomer cements (GIC) has been long established, and related to the release of fluoride ions from the restorative material. Diffusion of additional ions from GIC, like calcium, and phosphate has an additional effect on remineralized dentin in vivo in permanent teeth (26) . Those results are in agreement with others studies (27,28) , which showed significant remineralization effect of Nano glass ionomer on dentin.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant bond is therefore not weak. Strong and significant bonding of glass ionomers to underlying tooth structure is due to chemical bonding interactions with the mineral phase of underlying tooth [23] aided by the evident ion-exchanges [2]. It ought to be noted that reactive, sclerotic dentine under carious lesions has a different mineral composition as compared to non-carious, non-deminerlized dentine substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, fluorine showed a dramatic presence within the surrounding tooth after four years in vivo. Calcium exchange into the restorative material was also observed [2]. Ions such as strontium, alumina and fluorine migrating from the glass ionomer restorative into the surrounding dental structures may be presumed to possess a bactericidal/anti-cariogenic influence and may also enhance remineralization.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations